ANALISIS PERAN STAKEHOLDER PEMERINTAH DAERAH DALAM STRATEGI KOMUNIKASI CITY BRANDING: “PONOROGO ETHNIC ART OF JAVA” - Setiawan, Veri; Nurhana Marantika; Mohammad Abdul Hamid Alfarizi Al Ma'arif Nur (Jurnal Penelitian Ilmiah INTAJ, 2024)
Ponorogo Regency is one of Indonesia's cities rich in Javanese ethnic culture and art. One aspect that becomes potential in City branding Ponorogo is the tagline "Ethnic Art of Java", which reflects the richness of traditional Javanese culture and art in this city. This study aims to determine the role of local government stakeholders of Ponorogo Regency in communicating the city branding of Ponorogo Regency “Ethnic Art of Java". This research is qualitative descriptive method research with a case study approach. The results of this study show that Ponorogo city branding communication uses three communication channels: Primary Communication, Secondary Communication, and Tertiary Communication. The implementation of Primary Communication city branding of Ponorogo Regency can be seen in the addition of tourist attractions in Ponorogo Regency, improving road access to tourism in Ponorogo Regency, and forming a “Ponorogo Creative Team”. The application of Secondary Communication city branding for Ponorogo Regency can be seen in tourism marketing by making a calendar of Ponorogo Regency activities, installing promotional tools in various places, making various media relations, and making logo designs on several Ponorogo Regency activities. The implementation of Tertiary Communication for Ponorogo Regency "Ethnic Art of Java" can be observed by strengthening the media by evaluating publications every month, creating a social media monitoring system, and participating in the Ponorogo community in every Ponorogo Regency event.